Adherence to COVID-19 preventive measures and associated factors among high school students in Northwest Ethiopia: a cross-sectional study - Habtamu Tadesse Gudeta; Yordanos Jemberu; Shelema Likassa Nagari (BMJ Open Respiratory Research)
Background The novel coronavirus disease 2019 (COVID-19) is a respiratory infection that is spreading worldwide. The WHO has recommended public health preventive measures for COVID-19 prevention and control. Adherence to COVID-19 preventive measures is important for disease prevention and control of the disease’s spread. So, implementing preventive measures plays an essential role in reducing the spread of COVID-19 infection. This study aimed to assess the adherence status toward COVID-19 preventive measures and associated factors among high school students.Methods 528 high school students participated in an institutional-based cross-sectional study. A multistage sampling technique and a systematic random sampling method were applied to select the study participants. The data was entered into EpiData V.3.1 and then exported to SPSS V.23 for analysis. Bivariate and multivariable logistic regressions were computed. The significance of the association was declared by a 95% CI of adjusted OR (AOR) and a p value<0.05 in the multivariate model.Result A total of 528 respondents participated in the study, with a 100% response rate. The overall adherence level of high school students toward COVID-19 prevention measures was 110 (20.8%, 95% CI: 17.4%, 24.6%). The mean(±SD) age of the respondents was 18 (SD 11±2) years, which ranges from 16 to 24 years, and 387 (73.3%) were in the age group of 19–20 years, The majority of the students (418; 79.2%, 95% CI: 75.4, 82.6) had poor adherence to COVID-19 preventive measures. 345 (65.3%) had good knowledge, 328 (62.1%) had unfavourable attitudes and 390 (73.9%) had poor risk perception for COVID-19 preventive measures. This study revealed that most (89.9%) of the high school students did not maintain a physical distance of 2 m away, 84.4% of the students had no regular handwashing practice, majority 71.4% of the students did not use facemasks/covered their face during coughing and 62.9% of the students had no face mask and 54% of the students did not use sanitiser or alcohol per recommendation. This study revealed that sex (AOR: 2.42, 95% CI: 1.46, 4.02), attitude (AOR: 4.04, 95% CI: 2.45, 6.68) and risk perception (AOR: 7.60, 95% CI: 4.62, 12.54) were significantly associated with poor adherence toward COVID-19 prevention measures.Conclusion This study’s findings revealed that adherence to COVID-19 preventive measures among high school students was very low. Therefore, promoting adherence to COVID-19 preventive measures demands awareness creation and risk communication to build an appropriate level of knowledge, attitude and risk perception.